PENGEMBANGAN MODUL MATEMATIKA 3 DENGAN PENDEKATAN KONTEKSTUAL UNTUK MEMFASILITASI PEMAHAMAN KONSEP DAN KEMANDIRIAN BELAJAR MAHASISWA PGSD - Danuri . (Universitas PGRI Yogyakarta, 2016)
This paper is aimed to create a learning media in the form of a module as a sourceof mathematics learning based on contextual approach to PGSD student in order tofacilitate them to understand the concept and the student independence learning in terms ofstudents responses’ aspects to the moduledeveloped. This research can be classified as aResearch and Development (R & D) using ADDIE (Analysis, Design, Development,Implementation, and Evaluation) model with the mathematics module product forelementary school (SD / MI)based on contextual approach. The Development is donethrough several stages of analysis, design, development,implementation, and evaluation.The development model used in this research is the procedural development. It is adescriptive model, which outlinesthe steps and followed bycreating a product. The resultshowed that the CTL approach module got ‘good’ assessment by the validator with theeligibility percentage 82.6% for ideal contents and 80.35% for the appearance and languageused.After using the CTL approach module,theunderstanding conceptof studentsincreased.It was proved by the increasing of the average score for both pre-test and posttest.The earliest average is 47 and it became 92. The students’ response can be classifiedasa positive category with ideal percentage 88.4%Keywords: Module, Contextual, Concept understanding, and Independence Learning.